Scolex morphology of monozoic tapeworms (Caryophyllidea) from the Nearctic Region: taxonomic and evolutionary implications - Oros, Mikuláš; Uhrovič, Dalibor; Choudhury, Anindo; Mackiewicz, John S; Scholz, Tomáš (Folia parasitologica, 2020)
A comparative study of the scoleces of monozoic tapeworms (Cestoda: Caryophyllidea), parasites of catostomid and cyprinid fishes (Teleostei: Cypriniformes) in the Nearctic Region, was carried out using light and scanning electron microscopy. Scoleces of 22 genera of North American caryophyllideans were characterised and their importance for taxonomy, classification and phylogenetic studies was critically reviewed. Nearctic genera exhibit a much higher variation in the shape and form of scoleces compared with taxa in other biogeographical regions. The following basic scolex types can be recognised in Nearctic caryophyllideans: monobothriate (Promonobothrium Mackiewicz, 1968), loculotruncate (Promonobothrium, Dieffluvium Williams, 1978), bothrioloculodiscate (Archigetes Leuckart, 1878, Janiszewskella Mackiewicz et Deutsch, 1976, Penarchigetes Mackiewicz, 1969, Pseudoglaridacris Oros, Uhrovič et Scholz, 2018), fixomegabothriate (Capingens Hunter, 1927), bulbate and bulboacuminate (Atractolytocestus Anthony, 1958), cuneiloculate (Hypocaryophyllaeus Hunter, 1927, Rowardleus Mackiewicz et Deutsch, 1976, Spartoides Hunter, 1929), biacetabulate, bulboloculate, bothrioloculodiscate (Biacetabulum Hunter, 1927), tholate (Hunterella Mackiewicz et McCrae, 1962), cuneifimbriate (Khawia Hsü, 1935), cuneiform (Calentinella Mackiewicz, 1974, Caryophyllaeides Nybelin, 1922, Edlintonia Mackiewicz, 1970), hastate (Pseudolytocestus Hunter, 1929), loculotholate (Bialovarium Fischthal, 1953, Pliovitellaria Fischthal, 1951), and cuneiformoloculate (Glaridacris Cooper, 1920, Isoglaridacris Mackiewicz, 1965). The same type of scolex may be shared by species of different genera or families and species of the same genus can have a scolex of conspicuously different morphology, e.g. in Promonobothrium. Scolex morphology may be therefore of limited use in generic designation.
Keywords: máloostní; Animals; mikroskopie elektronová rastrovací; Biological Evolution; Cypriniformes; Microscopy, Electron, Scanning; biologická evoluce; Cestoda; zvířata